Human-Scale Whole-Organ Bioengineering for Liver Transplantation: A Regenerative Medicine Approach - Yagi, Hiroshi; Fukumitsu, Ken; Fukuda, Kazumasa; Kitago, Minoru; Shinoda, Masahiro; Obara, Hideaki; Itano, Osamu; Kawachi, Shigeyuki; Tanabe, Minoru; Coudriet, Gina M.; Piganelli, Jon D.; Gilbert, Thomas W.; et al. (Cell transplantation, 2013)
At this time, the only definitive treatment of hepatic failure is liver transplantation. However, transplantation has been limited by the severely limited supply of human donor livers. Alternatively, a regenerative medicine approach has been recently proposed in rodents that describe the production of three-dimensional whole-organ scaffolds for assembly of engineered complete organs. In the present study, we describe the decellularization of porcine livers to generate liver constructs at a scale that can be clinically relevant. Adult ischemic porcine livers were successfully decellularized using a customized perfusion protocol, the decellularization process preserved the ultrastructural extracellular matrix components, functional characteristics of the native microvascular and the bile drainage network of the liver, and growth factors necessary for angiogenesis and liver regeneration. Furthermore, isolated hepatocytes engrafted and reorganized in the porcine decellularized livers using a human-sized organ culture system. These results provide proof-of-principle for the generation of a human-sized, three-dimensional organ scaffold as a potential structure for human liver grafts reconstruction for transplantation to treat liver disease.